ІНЖИНІРИНГ-МЕНЮ ЯК ДІЄВИЙ АНАЛІТИЧНИЙ ІНСТРУМЕНТ ПІДВИЩЕННЯ ЕФЕКТИВНОСТІ ДІЯЛЬНОСТІ РЕСТОРАНУ - Ivanenko, Valentyna (Zhytomyr Ivan Franko State University, 2025)
The article examines menu engineering as an effective analytical tool for enhancing the performance and profitability of restaurant enterprises under conditions of economic instability. The relevance of the study is driven by rising food and operating costs, inflationary pressure, changes in consumer behavior, and increased competition in the restaurant industry. In this context, managing profitability at the level of individual menu items becomes a critical managerial task rather than focusing solely on overall financial results. The study systematizes theoretical approaches to menu analysis developed by both international and Ukrainian scholars, with particular attention to the models proposed by Miller, Kasavana and Smith, and Pavesic. The evolution of menu engineering is traced from traditional analyses based on food cost percentage and sales volume to more advanced models incorporating contribution margin and weighted profit contribution. It is demonstrated that reliance on a single evaluation criterion does not provide an adequate assessment of menu performance, whereas the combined application of multiple models improves the quality of managerial decision-making. The article identifies and substantiates the key functions of menu engineering, including analytical, cost-control, marketing, planning, and staff management functions. Menu engineering is conceptualized as an integrated management tool that combines principles of managerial accounting, marketing analytics, and behavioral economics. Special emphasis is placed on the practical importance of regular menu analysis for pricing adjustments, recipe optimization, targeted promotion of high-margin items, and the elimination of low-performing dishes. The study also highlights the modern interpretation of menu engineering, which extends beyond financial analysis to include menu design, item placement, visual cues, and neuromarketing techniques that influence customer choice. The findings confirm that systematic application of menu engineering contributes to improved restaurant profitability without significant increases in operational costs.